Rebellious Enthusiasm, Ambivalent Forms: On Freedom and Bondage in Tyehimba Jess’s Olio - Molly McCracken (European Journal of American Studies)
This article considers Tyehimba Jess’s representation of the lives of several historical African American musicians from the post-emancipation period in his 2016 collection Olio. Reading Olio in the context of African American musical traditions, it considers how Jess’s syncopated sonnet forms appropriate and contest historical instances of white supremacy to undermine the dehumanizing logics of plantocracy. At the same time, it explores how the collection’s three-dimensional forms materialize feelings of constraint to reveal the embeddedness of antiblackness in American popular culture, and the fragility of liberty into the twentieth century and beyond. While Olio reifies the tension between freedom and bondage in the post-bellum nation, this paper argues that Jess’s archival recuperation of elided historical figures and innovative configuration of sonnet form demonstrate an ethos of creativity, as it envisions alternative forms of community and autonomy through poetry and music.